TYPOLOGY AND STAGES OF THE TEACHING EXERCISE - Vasile PANICO PANICO; Violeta ȚURCAN (Acta et Commentationes, Sciences of Education, 2019)
The study is devoted to the analysis and development of concept exercise. This paper reflectsthe grounds/scientific criteria typology of exercises: components of personality structure, types of socialactivities, educational objectives, components of social culture reflected in the content of education,stages of educational material properties, the paper describes and characterizes the stages/phases of theexercise.